MODIFIKASI BET MENINGKATKAN KETERAMPILAN BACKHAND TENIS MEJA SISWA MA - Uswatun Hasanah; Subakti Subakti; Sukarman Sukarman (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
ABSTRACT Backhand stroke skill is one of the essential basic techniques in table tennis that students need to master in physical education learning. However, the learning process in schools often faces limitations in facilities, particularly the limited number of paddles, which reduces students’ opportunities to practice optimally. This study aimed to analyze the effectiveness of using modified paddles to improve backhand stroke skills in table tennis among tenth-grade students of MA NW Pringgarata in 2023. The study employed a classroom action research method consisting of planning, action implementation, observation, and reflection stages. The research subjects consisted of 10 students. The action was carried out through learning activities using modified paddles made from plywood soft wood coated with synthetic polyester fabric. The research instruments included a backhand stroke skill test, a student participation observation sheet, and a student attitude observation sheet. Data were analyzed descriptively using quantitative analysis based on mean scores and learning mastery percentages. The results showed that the use of modified paddles was able to improve backhand stroke skills, student participation, and student attitudes during the learning process. The use of modified equipment also helped create a more active and adaptive learning environment suitable for schools with limited sports facilities. ABSTRAK Keterampilan pukulan backhand merupakan salah satu teknik dasar penting dalam permainan tenis meja yang perlu dikuasai siswa dalam pembelajaran pendidikan jasmani. Namun, proses pembelajaran di sekolah sering menghadapi kendala keterbatasan sarana, khususnya jumlah bet yang terbatas sehingga kesempatan praktik siswa menjadi kurang optimal. Penelitian ini bertujuan menganalisis efektivitas penggunaan alat modifikasi bet dalam meningkatkan keterampilan pukulan backhand tenis meja pada siswa kelas X MA NW Pringgarata Tahun 2023. Penelitian menggunakan metode penelitian tindakan kelas dengan tahapan perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian berjumlah 10 siswa. Tindakan dilakukan melalui pembelajaran menggunakan bet modifikasi berbahan dasar plywood soft wood yang dilapisi kain sintetis jenis polyester. Instrumen penelitian terdiri atas tes keterampilan pukulan backhand, lembar observasi partisipasi siswa, dan lembar observasi sikap siswa. Analisis data dilakukan secara deskriptif kuantitatif berdasarkan nilai rata-rata dan persentase ketuntasan belajar. Hasil penelitian menunjukkan bahwa penggunaan bet modifikasi mampu meningkatkan keterampilan pukulan backhand, partisipasi, dan sikap siswa selama pembelajaran berlangsung. Penggunaan alat modifikasi juga membantu menciptakan pembelajaran yang lebih aktif, adaptif, dan sesuai diterapkan pada sekolah dengan keterbatasan fasilitas olahraga.